(untitled) (The Review of Diabetic Studies, 2025)
Medical errors in pre-hospital emergency settings represent a critical threat to patient safety and care outcomes. This review aims to analyze the frequency, types, and underlying causes of such errors among paramedics and emergency medicine practitioners, with emphasis on human, environmental, and systemic contributors. Through an extensive synthesis of recent studies (2016–2025), the review identifies procedural errors, communication breakdowns, delays in interventions, and medication administration mistakes as recurrent patterns. Human factors such as fatigue, stress, and cognitive overload, combined with environmental challenges like poor lighting, space constraints, and high noise levels, are major risk amplifiers. Moreover, organizational shortcomings—such as lack of standardized protocols, insufficient training, and ambiguous role delineation—further exacerbate risk in dynamic field conditions. By integrating insights from human factors engineering, systems theory, and resilience in emergency medicine, this review proposes an evidence-based framework for error reduction and patient safety enhancement. The paper concludes with strategies for continuous learning, simulation-based training, and environmental design improvements to minimize preventable harm in pre-hospital care.